Pengendalian Turover Intention Guru Pendidikan Anak Usia Dini Melalui Penguatan Komitmen Organisasional - Aisyah Nur Atika; Nunik Yulianti (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2023)
The research objectives developed from the problems mentioned above are: To analyze the effect of work motivation, compensation, and workload on controlling turnover intention, To analyze the effect of work motivation, compensation, and workload on organizational commitment, To analyze the effect of work motivation, compensation, and workload on controlling turnover intention through organizational commitment. The population of this study were all PAUD teachers in Jember Regency, with a total population of 3718 people. Based on the notation of the Slovin sample size formula, it was determined that the sample to be examined was 5% sample size 118,840 with a 9% margin of error rounded off by 119. The sampling technique used was Proportional Random Sampling. The research analysis tool uses SEM AMOS. The regression coefficient of work motivation on Organizational Commitment is 0.47 with a C.R. of 3.358, and a p-value (0.000) means it is smaller than 0.05. This shows that work motivation positively and significantly affects organizational commitment. The regression coefficient of compensation for Organizational Commitment is 0.18 with a C.R. of 3.409, and the p-value (0.000) means it is smaller than 0.05. The value of motivation has a higher impact on preventing teacher intentions (to stop working (Turnover intention), so PAUD managers in Jember Regency should pay attention to the needs of PAUD teachers, including their existence, relationships, and career development to prevent and inhibit the teacher's desire or intention to quit work, in other words paying attention to the fulfilment of the wishes of an early childhood teacher in Jember Regency can prevent the teacher's expectation that he will not leave his job or the organization he works in. The results of this study have contributed to the depth of organizational commitment theory which refers to the teacher's attachment to the organization related to the attitude and behaviour of the teachers while working in PAUD institutions.